2004
DOI: 10.1016/s0022-5223(03)01192-9
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and lidocaine: a new concept in nondepolarizing surgical myocardial arrest, protection, and preservation

Abstract: We conclude that adenosine and lidocaine polarizing cardioplegic solution confers superior cardiac protection during arrest and recovery compared with hyperkalemic depolarizing St Thomas' Hospital cardioplegic solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 40 publications
5
114
0
5
Order By: Relevance
“…Because increased K ϩ channel activation and rapid action potential duration shortening are known to cause arrhythmias (9), the AL combination may "clamp" ischemic cells at more polarized potentials than either Adeno or Lido alone (12). If left "unchecked," depolarization of the resting membrane potential could lead to chaotic firing of some cells in the ischemic region and act as a potential substrate for arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because increased K ϩ channel activation and rapid action potential duration shortening are known to cause arrhythmias (9), the AL combination may "clamp" ischemic cells at more polarized potentials than either Adeno or Lido alone (12). If left "unchecked," depolarization of the resting membrane potential could lead to chaotic firing of some cells in the ischemic region and act as a potential substrate for arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study design therefore is very different from Homeister et al (21), who administered an intravenous bolus of Lido in open-chested dogs 1 min before a 90-min occlusion of the left circumflex coronary artery and again 1 min before reperfusion, immediately followed by adenosine infusion at reperfusion and continued for 1 h. In the present study, AL was administered simultaneously in a single preparation 5 min before and during regional ischemia, not separately and sequentially. Moreover, we (12) have recently reported that, at higher concentrations, the single combination of AL acts as a highly effective nondepolarizing surgical cardioplegia that arrests the heart in asystole by "clamping" the membrane potential in its resting state at around Ϫ83 mV. We report that an intravenous infusion of an AL solution administered 5 min before and 30 min during ischemia rat protects from death, ventricular arrhythmias, and cell necrosis in the rat model of regional ischemia.…”
mentioning
confidence: 81%
“…Significant time/group interaction compared to both sham groups (analysis of variance); b significant time/group interaction compared to hemorrhage control (analysis of variance); c significant compared to hemorrhage; d average mean level significantly different during reperfusion between hemorrhage groups. (23). Adenosine alone exerts anti-inflammatory effects (16,24,25), whereas lidocaine is a known free radical scavenger (26) and combined as adenocaine they are more powerful at reducing infarct size and the priming and activations of neutrophils than either drug alone (7,27).…”
Section: Whole Blood Resuscitationmentioning
confidence: 99%
“…In an animal model of SIRS, deoxycoformycine, an inhibitor of adenosine deaminase that increases adenosine levels in the extracellular spaces, has been shown to improve survival time and suppresses the inflammatory response indices (32). Furthermore, activation of A2A receptors by adenosine confers antiinflammatory properties (33,34), and exogenous adenosine has beneficial effects on myocardium protection during coronary artery bypass surgery in humans (35) and during experimental myocardium arrest (36). High levels of exogenous adenosine also inhibit bleeding, probably because of its antifibrinolytic effects (37).…”
Section: Discussionmentioning
confidence: 99%